SATU UNTUK TIGA : HUNIAN MULTIGENERASI - Musselina Oktavanya Widiyanto; Nina Carina (Jurusan Arsitektur dan Perencanaan, 2021)
Dwelling is an essential form of conscious human activity. The form, aesthetics or beauty, and organization of environment that build become part of how a person lives. The concept of dwelling itself closely related to time and space. Therefore, the concept may shift or replaced according to the phenomena that occurred during the period of time. It is the same thing that we feel today in the presence of COVID – 19. Newly promoted health protocols, such as social isolation creates domino effect. Outdoor activities must be carried out in the dwelling, causing the shelter to need a place to accommodate these new needs. This also creates new problems with the existence of various age groups in one family. With the aim of creating a family ecosystem in one dwelling based on issue of social isolation that interferes with how to interact, the Architectural Programming (Cherry, 2009) method are applied and also points from MASS : Designing senior housing for safe interaction (2020). The application of this method produces programs that suit the needs of each age group in a family as well as paying attention to initial issue, in this case social isolation. One for Three: Multigenerational House is a new shared space concept that combines the needs of three generation and attention to safe interaction in social isolation. In addition, One for Three: Multi-generational House retains the value of independence and identity in all group of age. Keywords : group of age; multigeneration; safe interaction; shared space; social isolationAbstrak Berhuni merupakan salah satu bentuk kegiatan manusia secara sadar yang esensial. Bentuk, estetika, dan organisasi lingkungan binaan semuanya menjadi bagian dari bagaimana seseorang tinggal. Konsep berhuni memiliki kaitan yang erat dengan waktu dan ruang. Oleh karena itu, konsepnya akan tergeser atau digantikan sesuai dengan fenomena yang terjadi pada kurun waktu yang dimaksud. Sama hal nya yang kita rasakan saat ini yaitu adanya COVID – 19. Protokol kesehatan yang baru digalakan seperti sosial isolation dan menimbulkan efek domino. Kegiatan outdoor harus dilakukan di dalam hunian sehingga menyebabkan hunian memerlukan tempat untuk menampung kebutuhan baru tersebut. Hal ini juga menimbulkan masalah baru dengan adanya kelompok usia yang bervariasi pada satu keluarga. Dengan tujuan menciptakan ekosistem keluarga dalam satu hunian berdasarkan isu terhadap social isolation yang mengganggu cara berinteraksi, maka diterapkan metode Architectural Programming (Cherry, 2009) dan poin dari MASS : Designing senior housing for safe interaction (2020). Penerapan metode ini kemudian menghasilkan program yang sesuai dengan kebutuhan setiap kelompok usia dalam suatu keluarga, serta memperhatikan isu awal yaitu social isolation. Satu untuk Tiga : Hunian Multigenerasi merupakan konsep berhuni shared space yang baru dengan menyatukan kebutuhan tiga generasi dan memperhatikan poin safe interaction in social isolation. Selain itu, . Satu untuk Tiga : Hunian Multigenerasi tetap mempertahankan nilai kemandirian dan identitas pada segala usia.